Program Discovery Pada Calon Pasangan Pengantin - Veny Mulyani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas AKI Semarang, 2021)
The purpose of this study was to examine effectiveness of discovery program in increasing Future Orientation (FO) specifically in marriage and family perspectives for prospective brides and grooms. Discovery program was being performed in 5 (five) sessions a day. Discovery program in this research had been attended by 30 (thirty) prospective brides and grooms. The results of this study are in accordance with the hypothesis that there are differences in FO specifically in marriage and family perspectives scores before and after doing discovery program (t = -2.811 significance 0.009<Î± 0.01). Afterdoing discovery program, the mean depression score was 80.93 and beforedoing discovery program themeanscore of depression was 78.37. Discovery program can increase FO specifically in marriage and family perspectives for prospective brides and grooms. FO specifically in marriage and family perspectives after doing discovery program increased higher than before doing discovery program.